The suboptimal structures find the optimal RNAs: homology search for bacterial non-coding RNAs using suboptimal RNA structures - Pánek, Josef; Krásny, Libor; Bobek, Jan; Jezková, Edita; Korelusová, Jana; Vohradsky, Jirí (Nucleic acids research, 2011)
Non-coding RNAs (ncRNAs) are regulatory molecules encoded in the intergenic or intragenic regions of the genome. In prokaryotes, biocomputational identification of homologs of known ncRNAs in other species often fails due to weakly evolutionarily conserved sequences, structures, synteny and genome localization, except in the case of evolutionarily closely related species. To eliminate results from weak conservation, we focused on RNA structure, which is the most conserved ncRNA property. Analysis of the structure of one of the few well-studied bacterial ncRNAs, 6S RNA, demonstrated that unlike optimal and consensus structures, suboptimal structures are capable of capturing RNA homology even in divergent bacterial species. A computational procedure for the identification of homologous ncRNAs using suboptimal structures was created. The suggested procedure was applied to strongly divergent bacterial species and was capable of identifying homologous ncRNAs.
Keywords: nekódující RNA; bakteriální RNA; sekvence nukleotidů; Molecular Sequence Data; molekulární sekvence - údaje; konformace nukleové kyseliny; Base Sequence; sekvenční homologie nukleových kyselin; Nucleic Acid Conformation; RNA, Untranslated; Sequence Homology, Nucleic Acid; RNA, Bacterial; Streptomyces; Mycobacterium